Kreativitas Guru dalam Meningkatkan Motivasi Belajar Siswa Pada Musim Pandemi Covid-19 di MI Ma’arif NU Karangasem Purbalingga - Yan Ekawati; Novan Ardy Wiyani (Jurnal Kependidikan, 2020)
This study aims to describe the creativity of teachers in an effort to increase student learning motivation during the Covid-19 pandemic season at MI Ma'arif NU Karangasem Purbalingga. This research uses a qualitative approach, case study method. Data collection techniques that researchers use are interviews and observation. Based on the results of research at MI Ma'arif NU Karangasem Purbalingga, teacher creativity in increasing student learning motivation during the Covid-19 pandemic season, including: 1) Teacher creativity in paying attention to students; 2) Teacher creativity in choosing and using appropriate learning methods. 3) Teacher creativity in selecting and using learning media; 4) the creativity of teachers in developing learning resources; 5) The creativity of teachers in conducting assessments; and 6) The creativity of teachers in appreciating and utilizing student work.